O Contemporâneo no Museu de Arte Contemporânea do Paraná - Rocha, Ana Carolina dos Santos [UNIFESP] (2024)
This dissertation investigates the complexity of the concept of the contemporary in the context of the Museum of Contemporary Art of Paraná (MAC Paraná), where the author served as director from 2019 to 2022. The research aims to analyze the intersections between contemporary art, critical museology, and decolonial debates. It seeks to understand how MAC Paraná positions itself in defining the contemporary within a context marked by social and cultural inequalities. The methodology adopted is based on two main questions: the decolonial debate and its possible practical application in museum management, and the relationship between institutional memory and the concept of contemporaneity. Through a critical analysis of acquisition policies and exhibitions, the dissertation proposes a dialogue between theory and practice, highlighting how contemporary museology can act as an agent of social transformation. Reflections on the sustainability of the implemented changes reveal the need for a continuous commitment to diversity and a critique of hegemonic narratives. The research concludes that MAC Paraná, like many public museums in Brazil, must balance its social role with the necessity of survival in a context of cultural commodification. By incorporating decolonial debates into its management, the museum can assert itself as a space of resistance and innovation, contributing to constructing new artistic narratives that challenge existing power structures.